Struktura fizyczna gruntu, zawartość substancji organicznej oraz skład chemiczny gleb w podłożach 21 stanowisk zieleni miejskiej na terenie Poznania. Część II. Zawartość substancji organicznej w podłożu. Odczyn gleby - Łukasiewicz, Szymon (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2011)
The present article is the continuation of a four-part series of publications describing the condition of soil environment in the area of broadly understood centre of Poznań. It presents the content of organic substance and the reaction of subsoils collected from under horse chestnuts (Aesculus hippocastanum) growing in 21 locations in the city. The methodology of sample collection has been described in Part 1.
Keywords: Physical structure of land; Urban soils; Content of organic substances; Humus; Horse chestnut; Aesculus hippocastanum L.